The Charmed Circle : Joseph II and the 'Five Princesses,' 1765-1790 - Gates-Coon, Rebecca (Book collections on Project MUSE., 2015)
"In late eighteenth-century Vienna, a remarkable coterie of five aristocratic women, popularly known as the 'five princesses, ' achieved social preeminence and acclaim as close associates of the reforming Habsburg Emperor Joseph II. They were Princess Maria Josepha Clary; Princess Maria Sidonia Kinsky; Princess Maria Leopoldine Liechtenstein; Countess, subsequently Princess, Maria Leopoldine Kaunitz; and Princess Maria Eleonore Liechtenstein. During the Viennese social season, members of the group made their way several times each week to the inner city palace of one of the 'Dames, ' as members of the group called themselves. Through analysis of the correspondence of these women and of the published and unpublished commentaries of their contemporaries, this study scrutinizes the activities of this select group of women during the co-regency period (1765-1780) when Joseph shared responsibility with his mother, Maria Theresia, and during Joseph's decade as sole ruler (1780-1790) after Maria Theresia's death--years during which the women enjoyed their special position"--